Synergistic Effect of Bifidobacterium Pseudocatenulatum and Fructooligosaccharides Against Escherichia Coli - Lim, Long Chang (2004)

(untitled)
8 wild type strains of Bifidobacterium pseudocatenulatum and 4 commercial strains (B. pseudocatenulatum JCM 1200, B. infantis ATCC 15698, B. breve ATCC 26720 and B. longum BB536) were screened for inulinase activity on modified PY-0 and PY-I agar. Wild type B. pseudocatenulatum F117 and reference B. pseudocatenulatum JCM 1200 were determined to have the highest inulinase activity. This activity was apparently higher on PY-0 agar in comparison to PY-I agar. In batch cultivation, growth of B. pseudocatenulatum F 1 17 was enhanced in PY-0 medium (0.38 h-' and 2.64 x lo8 cfulrnL), compared to PY-G (0.48 h-' and 5.45 x lo8 cfulrnL) and PY-I medium (0.20 h" and 1.70 x lo8 cfulmL) from the respective, initial specific growth rate and maximum growth. Acetic, lactic and formic acid production was also found to be relatively higher in PY-0 medium (38.60 mM; 37.48 mM; 7.37 mM) compared to PY-G medium (11.95 mM; 22.77 mM; 5.91 mM) or PY-I medium (12.34 mM; 19.73 mM; 0 mM). In therapeutic study, the antagonistic effect against E. coli V157 by B. pseudocatenulatum F117 was contributed by pH lowering of the growth medium. This effect was especially intensified at pH below 5.0. Antagonistic effect found in PY-0 medium was greater compared to that of PY-G medium. The kinetics of antagonistic effect could be divided into two apparent phases. It was the condition before (first phase) and after (second phase) B. pseudocatenulatum F117 to achieve the maximum growth (lo9 cfu/mL), with relatively intense antagonistic effect at second phase. Organic acid was highly produced at second phase (PY-G medium: 45.5728.99 mM; PY-0 medium: 61.542 1 1.92 mM) rather than first phase (PY-G medium: 25.59k3.16; PY- 0 medium: 30.46k7.21 rnM) implicative of the importance of probiotic concentration for effective antagonism. Oligohctose was found to be able to stimulate the growth of B. pseudocatenulatum F117 and consequently shorten the time for the maximum growth to achieve, from 18 hr in PY-G medium to 12 hr in PY-0 medium. Besides, lactic acid production was initiated 6 hr earlier in PY-0 medium than to PY-G medium, which could be an added inhibitory advantage. With low bifidobacteria dose (10' cfu/mL), the antagonistic effect displayed was quite identical to a higher dose (lo8 cWmL) employed. B. pseudocatenulatum F1l7 was found to obtain the maximum growth in 18 hr for the both trial doses in either growth medium. In prophylactic study, PY-0 medium could not be observed to further enhance the antagonistic effect in PY-G medium. E. coli V157 (1 o8 cfu/mL) was unable to sustain and multiply to a higher population but decreased in numbers in either growth mediums. Finally, a higher oligofructose concentration (1.0 %) was shown to dramatically improve the antagonistic effect as compared to the lower concentration (0.5 %) used, in both therapeutic and prophylactic study. This effect was again due to an even higher amount of organic acids produced.